Perancangan Animasi 3D Pylo dan Sofie Mengenalkan Cara Berpikir Rasionalisme - Satria Putra, Nanda; Istiar Wardhana, Mitra; Fefiana Mustikasari, Bunga; Wardani, Nuril Kusuma (Politeknik Negeri Batam, 2024)
The era of Industry 4.0 integrates technology in physical, biological, and digital dimensions, introducing new complexities into our lives. However, the understanding of philosophy, especially rationalism, is often neglected in media. This study aims to design media that are contemporary and to test the media on audiences. To address this, 3D animation was adopted as a means to introduce the concept of rationalism in an engaging and easily understandable manner. The MDLC (Multimedia Development Life Cycle) method was used in developing the animated film